Role of CD5L and SRD5A2 as Prognostic Biomarkers for Hepatocellular Carcinoma - Luo Y (Dove Medical Press, 2021)
Yunxiu Luo,1,* Xiaopeng Huang,2,* Jiabin Zhan,3 Shuai Zhang2 1Department of Radiation Oncology, Hainan Cancer Hospital, Affiliated Cancer Hospital of Hainan Medical University, Haikou, 570311, Hainan Province, People’s Republic of China; 2Department of Radiation Oncology, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, Haikou, 570311, Hainan Province, People’s Republic of China; 3Department of Otolaryngology, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, Haikou, 570311, Hainan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiabin ZhanDepartment of Otolaryngology, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, Haikou, 570311, Hainan Province, People’s Republic of ChinaTel +86-18907669339Email jiabin2021hainan@163.comShuai Zhang Tel +86-1387642896Email 46370976@qq.comPurpose: Due to the limitations of currently available biomarkers, new biomarkers are needed to accurately predict the prognosis of patients with hepatocellular carcinoma (HCC) patients.Methods: In this study, we screened for differentially expressed genes (DEGs) in the tumor and the adjacent tissues using the four gene expression array (GSE14520, GSE45267, GSE121248, GSE62232) of the Gene Express Omnibus (GEO) database.Results: Subsequently, 47 overlapping DEGs were identified in four GEO datasets, which were mostly located on chromosomes 5q and 6q, distributed in the liver and CD105-positive endothelial cells, and closely related to HCC. Function enrichment revealed 47 DEGs were related to HCC, and involved in steroid /lipid /retinol metabolism, bile secretion and p53 signalling pathway. The Kaplan–Meier plotter analysis (http://www.kmplot.com/) identified 26 and 40 genes associated with the 5-year overall survival (OS) and relapse-free survival (RFS). We found that CD5L and SRD5A2 were independent prognostic factors for 5-year OS (P=0.036) and RFS (P=0.044) in HCC patients from GSE14520, respectively. Clinicopathological features including BCLC stage, cirrhosis, and risk signature for predicted metastasis were used to construct and validate a nomogram for 5-year OS with C-index of 0.732 and 0.717 in the training and validation cohort, respectively. SRD5A2, BCLC stage and gender was independent prognostic factors for RFS which were used to build a nomogram with the C-index of 0.666 and 0.682 in the training and validation cohort, respectively.Conclusion: CD5L can facilitate individualized, targeted therapy for HCC patients.Keywords: hepatocellular carcinoma, CD5L, prognostic, nomogram, SRD5A2